Nanodevices for Microwave and Millimeter Wave Applications - Huynen, Isabelle (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
The microwave and millimeter wave frequency range is nowadays widely exploited in a large variety of fields including (wireless) communications, security, radar, spectroscopy, but also astronomy and biomedical, to name a few. This Special Issue focuses on the interaction between the nanoscale dimensions and centimeter to millimeter wavelengths. This interaction has been proven to be efficient for the design and fabrication of devices showing enhanced performance. Novel contributions are welcome in the field of devices based on nanoscaled geometries and materials. Applications cover, but not are limited to, electronics, sensors, signal processing, imaging and metrology, all exploiting nanoscale/nanotechnology at microwave and millimeter waves. Contributions can take the form of short communications, regular or review papers.